US Cuba Policy after Bush: succession or transition?. (1st June 2008) - Wilkinson, Stephen
Abstract : For almost 50 years the United States has pursued a policy of bringing about regime change in Cuba, through a series of measures. The main plank of US policy - enduring though its historic rationale ended with the Cold War -has been the economic embargo, which has equally proved a failed strategy. With Castro's retirement, some observers believe that the US will find it easier to soften its line. President George W. Bush's official policy towards post-Castro Cuba is to prevent what is seen as a 'succession' of the one party Communist regime and to help instigate a 'transition' towards a western liberal free market model. The proposal might rather be reversed and applied to the United States itself: will the end of the George W. Bush presidency herald a succession of the embargo policy or will there be a 'transition' towards a different approach to the island? This article will examine some trends in the US that point in the direction of change, including public opinion in Florida and the attitudes of the current presidential candidates. It argues that this year, for the first time, Cuba may become an election issue in the US.